Răspuns :
a-b=34
3a+2b=187
a=b+34
3(b+34)+2b=187
3b+102+2b=187
5b=187-102
5b=85
b=85:5
b=17
a=b+34=17+34
a=51
3a+2b=187
a=b+34
3(b+34)+2b=187
3b+102+2b=187
5b=187-102
5b=85
b=85:5
b=17
a=b+34=17+34
a=51
Daca numerele sunt a si b atunci ,
a - b = 34 (pentru a > b)
3a +2b=187
inmultimi prima ecuatie cu 2 → 2a - 2b = 68 adunam acesta cu a 2-a ecuatie ...
3a + 2b = 187 +
2a - 2b = 68
5a = 255 → a = 51 iar b = 17
a - b = 34 (pentru a > b)
3a +2b=187
inmultimi prima ecuatie cu 2 → 2a - 2b = 68 adunam acesta cu a 2-a ecuatie ...
3a + 2b = 187 +
2a - 2b = 68
5a = 255 → a = 51 iar b = 17